The Effect of Training Methods and Agility on Reaction Speed Of Por and PKO FIKKM UNIMA Students - Richmond Piet Armando Pandey; Agustinus R. J. Sengkey; Eduard E. Kumenap (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research is an experimental research withThe research design used in this study is